(untitled) (Research, Society and Development, 2021)
The objective was to report a case of fetal maceration in a cat, approximately 3 years old, weighing 5.0 kg, no defined breed, who had received a contraceptive dose of medroxyprogesterone acetate post coverage. The patient was admitted to the University Veterinary Hospital of UFOB presenting. abdominal discomfort and fetid bloody vaginal discharge, with a history of application of the contraceptive. In the physical exam, although the parameters are not altered, it was noticed a large bilateral abdominal distension. Palpation showed an increase in uterine volume with presence of fluid and firm material. In the abdominal ultrasonography, bone structures of three fetuses were observed, with irregular silhouettes, and absence of heartbeat, thus showing that it was a fetal death with a maceration process. After clinical stabilization, the animal was submitted to ovariohysterectomy. Seven days after the surgical procedure, the patient was active, thus, the removal of stitches was performed, followed by medical discharge.